Social Hazards as Manifested Workplace Discrimination and Health (Vietnamese and Ukrainian Female and Male Migrants in Czechia) - Drbohlav, Dušan; Dzúrová, Dagmar (International journal of environmental research and public health, 2017)
Social hazards as one of the dimensions of workplace discrimination are a potential social determinant of health inequalities. The aim of this study was to investigate relations between self-reported health and social hazard characteristics (defined as-discrimination as such, violence or threat of violence, time pressure or work overload and risk of accident) among Vietnamese and Ukrainian migrants (males and females) in Czechia by age, education level and marital status. This study is based on data from a survey of 669 immigrants in Czechia in 2013. Logistic regression analysis indicates that the given independent variables (given social hazards and socio-demographic characteristics), as predictors of a quality of self-reported health are more important for immigrant females than for males, irrespective of citizenship, albeit only for some of them and to differing extents. We found out that being exposed to the selected social hazards in the workplace leads to worsening self-rated health, especially for females. On the other hand, there was no statistically significant relationship found between poor self-rated health and discrimination as such. Reality calls for more research and, consequently, better policies and practices in the field of health inequalities.
Keywords: Socioeconomic Factors; Young Adult; Workplace; social hazards; Ukraine; Male; logistic regression; zpráva o sobě; osoby s přechodným pobytem a migranti; mladý dospělý; Transients and Migrants; Česká republika; Vietnam; Czechia; Adult; Prejudice; socioekonomické faktory; dospělí; násilí; mužské pohlaví; self-reported health; discrimination; Marital Status; Violence; Emigrants and Immigrants; průzkumy a dotazníky; Czech Republic; questionnaire survey; workplace; Health Status; lidé; ženské pohlaví; Humans; Self Report; předsudek; emigranti a imigranti; zdravotní stav; Ukrajina; Vietnamese and Ukrainian immigrants; manželský stav; Female; Surveys and Questionnaires; lidé středního věku; pracoviště; Middle Aged